Hubungan Intimate Friendship dengan Self Disclosure pada Remaja - Gahara Kusuma Salsabila; Evi Afiati; Putri Dian Dia Conia (Program Studi Bimbingan dan Konseling, 2025)
This study aims to determine whether there is a relationship between the intimate friendship variable and the self-disclosure variable in adolescents at SMAN 2 Kota Serang. The method used is a quantitative approach with correlational techniques. Data were collected through a questionnaire based on eight dimensions of intimate friendship according to Sharabany (2008) and five aspects of self-disclosure according to Devito (2011, in Eka, 2024). A total of 240 students were randomly selected using random sampling techniques. The results of the analysis showed a correlation of 0.784 between intimate friendship and self-disclosure, and a significance level < 0.05 is 0.000. So it can be indicated that there is a strong relationship in the interpretation of the r value, meaning that the relationship is positive and significant between the two variables, which is 78.4%.